Endovascular repair of a juxtarenal saccular aneurysm using the Multilayer Flow Modulator: report of the first case performed in a Public Hospital in Brazil - Jaldin, Rodrigo Gibin [UNESP] (2014)
Endovascular aortic aneurysm repair (EVAR) involving renal and visceral arteries remains a great challenge. Several techniques have been developed over the time to treat juxtarenal, pararenal and thoracoabdominal aneurysms, highlighting the fenestrated and branched endografts, parallel prostheses as Chimney, Periscope and Sandwich Techniques and the use of flow modulation by multilayer stent. We report a case of saccular juxtarenal aortic aneurysm with high surgical risk for complex airway access due to a history of radical laryngectomy for laryngeal neoplasm. Due to chronic aorto-iliac obstructive disease, ostial stenosis of renal artery and limited diameter of the suprarenal aorta, we discarded options involving fenestrated/branched endografts and involving parallel prostheses techniques. We present this case as a therapeutic challenge and a successful treatment option in the short-term evaluation.